STATUS OF THE AUTONOMIC NERVOUS SYSTEM AND ULCER DISEASE OF THE STOMACH AND DUODENUM (Journal of Universal Science Research, 2024)
From modern perspectives, peptic ulcer disease is considered a multifactorial poly-etiological disease. The founder of the neurogenic concept of lesion development, G. Bergman, believed that the main role in the pathogenesis is played by functional disorders of the autonomic nervous system with the predominance of the vagus nerve tone. Disruption of the harmonious effect on the stomach of parasympathetic and sympathetic parts of the autonomic nervous system leads to the formation of ulcers. The disruption of the sympathetic innervation of the gastroduodenal complex plays a significant role in the development of morpho- functional changes. The flow of sympathetic pulses causes excessive excretion of catecholamines, leading to disruption of tissue trophic processes. Stress stimulates the function of the hypothalamus. This causes hypersecretion of hydrochloric acid and pepsin, hypermotorism and hypertonia of the stomach, spasm of the blood vessels and ischemia.